Estudo comparativo da eficácia da boretação sólida com a boretação a plasma na liga Ti6Al4V - Silva, Felipe Lopes Fonseca da (Universidade Federal de São Carlos, 2022)
Ti6Al4V alloy is one of the most widely used alloys in the biomedical field as an implant and in the aerospace field for structures. However, surface treatment of these alloys is extremely important, since in the biological field Ti6Al4V alloy contains aluminum and vanadium, which are toxic to the biological environment, while in industrial areas the surface properties of the material influence the performance of the structure. Boriding is one of the surface treatments that has been attracting the attention of researchers due to the properties acquired in materials after treatment, and the solid pack boriding and plasma paste boriding processes are the most widely used in economic and toxicological terms. This work aims to perform a comparative analysis of the surface properties acquired by the conventional pack boriding method and the plasma paste boriding method, which was developed in this work, on the Ti6Al4V alloy. In the first stage of this work, Ti6Al4V samples were treated by pack solid boriding at 750, 850, 950, and 1050ºC for 3 and 6 hours using the boriding agent Ekabor 2. Paste plasma boriding treatment was carried out in a vacuum reactor using a gas ratio of 40% H2, 40% N2 and 20% Ar with a boriding agent supplied by a solid paste rich in this element. The second stage involved the development of a plasma boriding treatment with solid paste, which included the study of four different pastes: paste 1 composed of 80% Ekabor 2® – 20% Na2B4O7, paste 2 with 100% Na2B4O7, paste 3 with 70% Na2B4O7 – 30% SiC, and paste 4 with 30% Na2B4O7 – 70% SiC. After being molded onto the samples, these pastes were subjected to a plasma treatment at 650°C for 3 hours. For the third stage of this work, the plasma boriding treatment was carried out at 650°C and 700°C for 3 and 6 hours respectively, using the paste that demonstrated the best results in terms of stability and characteristics of the formed layer. In the pack solid boriding process, boron diffusion was identified at temperatures of 850, 950, and 1050ºC in 3 and 6 hours, with the formation of a layer containing the TiB2 (titanium diboride) and TiB (titanium boride) phases. However, in all samples treated in the pack solid boriding process, the presence of pores and the formation of the TiO2 phase were observed. This oxide is formed due to the high affinity of oxygen for titanium, and this phase hinders the regular diffusion of boron in the substrate and weakens the layer. At 950ºC for 3 and 6 hours, the layers showed better regularity, thicknesses of 89.052 ± 5.462 µm and 76.107 ± 4.262 µm, surface hardness of 1247.9 ± 120.9 HV and 1025.4 ± 46.3 HV respectively, and the formation of TiB2 and TiB phases. In plasma boriding, the pastes with the highest concentrations of borax (Na2B4O7), pastes 2, 3, and 4, produced a layer without pores, with the formation of TiB2 and TiB phases, without the presence of the TiO2 phase. Paste 3 showed the best results, with a layer thickness of 11.602 ± 0.436 µm, a hardness of 663.9 ± 86.6 HV, and the presence of TiB2 and TiB phases. The condition of paste 3 was used for the development of the third stage of this work. It was observed that in terms of layer thickness, hardness, boron concentration, and phases formed, the treatments performed for 3 hours presented the best results at 650 and 700ºC, with a total layer thickness of 11.602 ± 0.436 µm and 6.429 ± 0.619 µm, respectively, with hardnesses of 663.9 ± 86.6 HV and 768.3 ± 50.7 HV, and TiB2 and TiB phases formed. The plasma boriding process showed better results compared to the solid process due to it managed to diffuse the boron, forming the desired layer with the TiB2 and TiB phases present, without defects or porosity, and without the formation of the TiO2 phase.
Comparative study of the effectiveness of solid boriding and plasma boriding on the Ti-6Al-4V alloy
Keywords: Ti6Al4V; Boretação sólida em caixa; Boretação a plasma com pasta; Pack solid boriding in box; Paste plasma boriding; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA; 9. Indústria, Inovação e Infraestrutura